Capacidade absortiva: conceito e suas variações de significados conforme diferentes áreas de conhecimento - Silva, Karina Machado da (2023)
The study of Absorptive Capacity (ACAP) in companies has been carried out since the mid- 1990s by national and international researchers. However, over this time, some discussions have arisen regarding the concept of ACAP and its possible variations of meanings. And to solve this problem, the present study has the general objective of analyzing whether there is a basic definition for the concept of absorptive capacity and a unique meaning linked to it or if there are variations of meaning to meet the needs of researchers who are in contact with the companies, and if so, what are the variations of this transformation. To respond to this objective, the qualitative and quantitative methodology was approached, initially adopting as methodological procedures a bibliographical research in the Capes journal portal, covering the Scielo and Web Of Science databases, resulting in a total of 70 studies for the database. Subsequently, a content analysis of these studies was carried out based on the author Bardin (1977, 2004, 2010) and with the help of the Iramuteq software, to analyze the research results more precisely. Therefore, after the analysis results, it was verified that there is a nucleus of the ACAP concept being used by the researchers, which refers to the initial concept of Cohen and Levinthal (1989, 1990) and Zahra and George (2002), being identified as the company's ability to acquire external knowledge, assimilate it with previous knowledge, transform and apply this knowledge. In this way, what happens is that the meaning of the ACAP concept ends up changing according to the area of knowledge of the research, and the meaning of the concept does not change according to the research language, according to the nationality of the researcher and because the study is theoretical or applied in companies, concluding that there are differences in the meaning of ACAP according to the research area that the study covers.